Kinetics of exchangeable protons in Z DNA: a UV resonance Raman study. - Laigle, A (1989)
We have studied the hydrogen-deuterium exchange kinetics of the exchangeable protons of the poly(dG-dC).poly(dG-dC) in the Z form of the polymer, using resonance Raman spectroscopy with 257 nm and 284 nm excitation wavelengths. In our experimental conditions (4.5 M NaCl, phosphate buffer pH7, 2 degrees C) the two amino protons and the imino proton of guanine are exchanged with the same exchange half-time of 13 min, whereas the two amino protons of cytosine are exchanged with the same exchange half-time of 51 min.